The influence of qualifications on women's work histories, employment status and earnings at age 33 - Elliott, Jane [Verfasser]; Dale, Angela [Verfasser]; Egerton, Muriel [Verfasser] (My University, 2001)
"This paper examines the relationship between women's qualifications and their labour-market participation up to the age of 33 for a cohort of women born in Great Britain in one week of March 1958. The period of the life-cycle on which the analysis focuses is one during which many women are attempting to juggle the competing demands of young children and employment. In Britain, with very limited institutional support for retaining employment during family formation, we examine the role which occupationally specific qualifications exert in helping women to return to paid employment. The second part of the paper focuses on the occupational attainment of women at age 33, operationalized using log hourly earnings. The earnings equations are corrected for possible selectivity bias into employment. The paper makes an important theoretical distinction between occupationally specific and non-occupational qualifications. We argue that, for women, occupational qualifications are associated with greater attachment to the labour-market following the birth of children. By including work history variables in the earnings equation we are also able to examine the consequences for women's wages of having time out of the labour market." (author's abstract, IAB-Doku) ((en))
Keywords: G 1.2.3.1 Potenziale; G 1.3.3 Bildungs- & Erwerbsbiografien; G 2.3.2 Arbeits- & Beschäftigungsverhältnisse; G 1.2.2.1 Lohn- & Tarifsysteme; I 2.2.1 Westeuropa; Erwerbstätige Frau; Qualifikationsniveau; Berufsverlauf; Lohnhöhe; Arbeitsmarktchance; Erwerbsunterbrechung; Quantitative Angaben; Großbritannien